Where Should the Elderly Live and Who Should Pay for their Care? A Study in Demographics and Geographical Economics - Thomas Aronsson; Sören Blomquist; Luca Micheletto (Uppsala University, Department of Economics, 2007)
There is a rich literature analyzing the problems that will arise as the share of elderly and retired in the population increases in the near future. However, the locational decisions among the elderly as well as their implications in terms of taxes/transfers and of allocation of responsibilities for elderly care between the federal and local levels have not received much attention. In this paper we aim at investigating these issues. For this purpose we explore a model where there is a big city and a set of small villages, and where congestion effects and agglomeration forces are at work at the level of the big city. We also assume that the population is divided between two groups of agents, workers and retired, which differ with respect to the degree of mobility. In the first part of the paper we study and characterize the inefficiencies that arise because of individuals free location choice in the context of a unitary government. In the second part of the paper we consider a fiscal federalism structure and we investigate the suitable instruments that are needed in order to decentralize the optimal allocation obtained under full centralization.
urn:nbn:se:uu:diva-25359
Keywords: D62; H42; H55; H77; J10; 330; agglomeration effects; congestion; elderly care; fiscal federalism; Bevölkerungsentwicklung; Alternde Bevölkerung; Altenhilfe; Wohnstandort; Finanzbeziehungen; Wirtschaftsmodell